2004
DOI: 10.1002/14651858.cd003978.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of prosthetic ankle-foot mechanisms after lower limb amputation

Abstract: There is insufficient evidence from high quality comparative studies for the overall superiority of any individual type of prosthetic ankle-foot mechanism. In high activity transfemoral amputees, there is limited evidence for the superiority of the Flex foot during level walking compared with the SACH foot in respect of energy cost and, gait efficiency. This benefit has only been confirmed in transtibial amputees during decline and incline walking and increased walking speeds. In prescribing prosthetic-ankle f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 37 publications
5
65
0
Order By: Relevance
“…We are not aware of any RCTs in prosthetic research, which is confirmed by the results of a recent systematic review of the entire prosthetic literature [96]. We therefore believe that the scale of Hofstad et al [90], accepted by the Cochrane Collaboration, is an appropriate tool to assess the methodological quality of clinical trials in prosthetics. The Hofstad checklist comprises 13 criteria for methodological quality that are all scored using one out of three possible levels: no = 0, yes = 1, or not applicable.…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 89%
See 3 more Smart Citations
“…We are not aware of any RCTs in prosthetic research, which is confirmed by the results of a recent systematic review of the entire prosthetic literature [96]. We therefore believe that the scale of Hofstad et al [90], accepted by the Cochrane Collaboration, is an appropriate tool to assess the methodological quality of clinical trials in prosthetics. The Hofstad checklist comprises 13 criteria for methodological quality that are all scored using one out of three possible levels: no = 0, yes = 1, or not applicable.…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 89%
“…or E.P.) using the checklist of a Cochrane Systematic Review on prosthetic ankle-foot mechanisms published by Hofstad et al [90]. It is based on two existing scales for methodological quality assessment of randomized controlled trials (RCTs) of van Tulder et al [91] and Verhagen et al [92] but was adapted to also evaluate internal and external validity as well as the risk of bias of nonrandomized studies as recommended by Downs and Black [93], Reisch et al [94], and Zaza et al [95].…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…It was assumed that this would reduce the metabolic energy cost while walking [2][3]. Whereas several studies have shown that prosthetic users subjectively choose the ESAR foot over the solid-ankle cushioned heel (SACH) foot [2], conflicting evidence is found with regard to its (clinically relevant) effect on metabolic energy cost [4][5][6]. Remarkably, however, the underlying effects of ESAR feet on the mechanics of walking have not yet been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%